A performer's perspective on three works for pianist and moving images : analysis with performance and practice strategies for Michel van der Aa's 'Transit', Nicole Lizée's 'Hitchcock Études', and 'Surface Tension' by Eve Egoyan and David Rokeby - Morano, Christopher (Université de Colombie-Britannique, 2017)
Interest in audio-visual works of art that are performed by a live pianist while integrating projected moving visual images has waxed and waned over a period of almost 300 years. The past twenty years or so has seen a re-emergence of this genre of classical music composition which places extra demands on the pianist performing these works. This dissertation explores the history of this genre, proposes a framework for analysis of these pieces, and examines from both analytical and performance perspectives three contrasting works for this medium: Michel van der Aa’s 'Transit', Nicole Lizée’s 'Hitchcock Études', and 'Surface Tension' by Eve Egoyan and David Rokeby. This research was